PS-058 Evaluation of clinical pharmacists' interventions in a cardiology department. (25th February 2017) - Chapet, N; Mathieu, B; Audurier, Y; Barry, G De; Jalabert, A; Renaudin, P; Breuker, C; Villiet, M; Castet-Nicolas, A
Abstract : Background: Previous studies have reported that clinical pharmacists improve medication safety. A clinical pharmacy team (1 senior pharmacist, 1 junior pharmacist, 7 student pharmacists) was deployed in cardiology units (79 beds) to develop medication reconciliation (MR), identify medication errors (ME) and optimise patients' pharmacotherapy. Purpose: The aim of this study was to describe and analyse pharmacists' interventions in cardiology units over 9 month and to evaluate their impact on the management of cardiovascular diseases. Material and methods: This work was a prospective, non-randomised, observational study performed between December 2015 and August 2016. Interventions were made during MR or during the prescriptions analysis in cardiology (1 intensive care, and 2 clinical units). Analysis criteria were number and type of ME, proportions of drugs involved in ME and the physicians' acceptance rate. A focus on cardiovascular ME was made to highlight interventions about management of heart failure (HF) and acute coronary syndrome (ACS). Results: A total of 532 interventions were performed for 339 patients. Mean (median) age was 70.4 (72) years. The 3 most frequent types of ME were incorrect dose (overdosage (107; 20.1%) and underdosage (96; 18%)), untreated indication (178; 33.5%) and inappropriate form of administration (52; 9.8%). 48.5% of pharmacists' interventions were identified by MR. The percentage of intervention accepted was 98.2% and concerned mostly treatments of the cardiovascular system (137; 25.8%), alimentary tract and metabolism (94; 17.7%), and nervous system (80; 15%). In the cardiovascular system, the most prevalent drugs therapy involved were statins (35; 25.6%), ACE inhibitors (21; 15.3%) and beta-blockers (18; 13.1%). 39 (28.5%) and 31 (22.6%) of interventions for cardiovascular drugs improved HF and ACS therapies, respectively. Conclusion: These results highlight a positive impact of the pharmacy team on reduction of ME. Prescription analysis and MR are 2 key points in avoiding medication discrepancies. The pharmacist has become a key member in the cardiology team. They are involved in therapeutic strategy, and most of the interventions concerned cardiovascular drugs. Moreover, half of these interventions involved treatment of HF and ACS, so pharmacists can improve the management of these chronic diseases. References and/or acknowledgements: Acknowledgements to cardiology teams. No conflict of interest